Inflammatory myofibroblastic tumours of the thorax: Radiologic and clinicopathological correlation - Irodi, Aparna; Chacko, Binita R; Prajapati, Anand; Prabhu, Anne J; Vimala, Leena R; Christopher, Devasahayam J; Gnanamuthu, Birla R (Indian Journal of Radiology and Imaging, 2020)
Context and Aims: Inflammatory myofibroblastic tumour (IMT) is a rare mesenchymal neoplasm with intermediate malignant potential. The aim of this study is to describe and compare the clinical presentation, computed tomography (CT) findings and anaplastic lymphoma kinase -1 (ALK-1) expression of IMT of the thorax in children and adults. We also sought to study the tumour behaviour after treatment on the follow-up imaging. Materials and Method: This is a retrospective observational study of 22 histopathologically proven cases of IMT in the thorax. The clinical parameters, CT findings, biopsy results, treatment received and follow-up were recorded. Statistical analysis was performed using Fisher’s exact test. Results: IMT of the thorax had diverse imaging appearances, presenting either as large invasive lung masses with or without calcifications or as smaller endobronchial lesions. Children commonly presented with long duration fever (P = 0.02) and large invasive lung masses (P = 0.026), whereas adults presented with long duration haemoptysis (P = 0.001) and endobronchial lesions or smaller lung parenchymal lesions. Calcifications were more common in children (P = 0.007). ALK-1 was positive in 40% of children and 18.2% of adults (P = 0.547). Endobronchial lesions showed a trend for ALK-1 negativity. Patients with bronchoscopic excision had local recurrence and patients with surgical wedge resection had metastatic brain lesions as compared to those with lobectomy and pneumonectomy (P = 0.0152). A patient with unresectable lung mass had malignant transformation to spindle cell sarcoma after 9.5 years. Conclusions: Thoracic IMT presents with some distinct clinical and CT findings in adults and children. The CT findings and management options have implications for prognosis. If resectable, lobectomy is a better option than wedge resection or bronchoscopic excision for preventing local recurrence and metastasis. IMT can undergo malignant transformation.
Keywords: Anaplastic lymphoma kinase-1; inflammatory myofibroblastic tumour; thorax